ФЕНОМЕН “ПАРТІЇ ВЛАДИ”: ТРАДИЦІЇ РАДЯНСЬКОЇ ПАРТІЙНОЇ РОБОТИ В ДІЯЛЬНОСТІ СУЧАСНОГО УКРАЇНСЬКОГО ПОЛІТИКУМУ (Zaporizhzhia Historical Review, 2021)
In article the author suggests to use the term “party in power” both in relation to public organization, and to a symbol of process of preservation of authority the party nomenclature of times Ukrainian SSR – the USSR.